Does alveolar soft-part sarcoma exhibit skeletal muscle differentiation? An immunocytochemical and biochemical study of myogenic regulatory protein expression - Wang, N. P.; Bacchi, C. E.; Jiang, J. J.; McNutt, M. A.; Gown, A. M. (Williams & Wilkins, 1996)
There has been persistent controversy regarding the nature of cell differentiation in alveolar soft-part sarcoma (ASPS) since its first description in 1952. Some studies suggest that ASPS might represent an unusual variant of skeletal muscle tumor, Given the availability of new monoclonal antibodies to probe for skeletal muscle differentiation and the rapid advance in immunocytochemical techniques for deparaffinized, formalin-fixed tissue sections, we wished to test the proposed hypothesis that ASPS might represent a new type of rhabdomyosarcoma Twelve archival samples of ASPS were retrieved, and we investigated the expression of two myogenic regulatory proteins, MyoD1 and myogenin, as rvell as other muscle-associated proteins, using sensitive immunocytochemical techniques. Despite the presence of desmin immunostaining in six ASPSs, no tumors were positive for either muscle actin or myoglobin Most importantly, no specimen showed nuclear expression of MyoD1 or myogenin, In 11 tumors, however, there was considerable granular immunostaining in the tumor cell cytoplasm with the anti-MyoD1 monoclonal antibody 5.8A, a phenomenon observed in various nonmuscle normal and neoplastic tissues with this antibody, To analyze the exact nature of immunostaining of MyoD1 and desmin in ASPS, biochemical analyses using available fresh frozen tumor tissue were performed, Although a 53-kDa band was noted with antidesmin antibody on Western blot analysis, no specific protein band that corresponds to the 45-kDa MyoD1 was detected with antibody 5.8A. These results confirm the presence of desmin in ASPS but argue against authentic expression of MyoD1, They also suggest that the cytoplasmic immunostaining observed with anti-MyoD1 antibody 5.8A most likely represents a nonspecific cross-reaction with an unknown cytoplasmic antigen, Considering the master role that MyoD1 and myogenin play in skeletal muscle commitment and differentiation and the lack of expression of these two proteins in ASPS as determined immunocytochemically and biochemically, we think that the histogenesis of ASPS remains unknown.
Keywords: actin; alveolar soft-part sarcoma; desmin; MyoD1; myogenic regulatory protein; myogenin; rhabdomyosarcoma